Enzymatic Incorporation of Oleic Acid into Refined Bleached and Deodorised Palm Olein - Liew, Han-Fang (2007)
High oleic oils are very much in demand. Nutritionally, they are perceived to reduce cardiac related diseases. Oxidatively, they are more stable than polyunsaturated oils. However, palm olein, with natural oleic content of less than 50%, the olein solidifies in temperate climate. This study was conducted to investigate the performance of lipases on oil substrate to obtain high oleic content cooking olein. In the first part of the work, the effect of several reaction conditions on lipase-aided acidolysis of palm olein with oleic acid was studied. Results showed no significant difference on the effect of molecular sieve added into acidolysis process. Studies on the other effects indicated that the optimal condition for T. Lanoginosa lipase was at 50 °C, 10 % (w/w) lipase loading and substrate concentration of 1:2 (POo:OA mole ratio). Eight hours was selected as the best reaction time. The acidolysis process also increased the slip melting point of palm olein after 8 h reaction with T. Lanoginosa lipase registering the largest increase (3.8 °C) compared to the initial unreacted mixture. The catalytic stability of T. Lanoginosa lipase, after being subjected to ten runs of repeated usage indicated that the lipase can be reused to produce fairly constant products on a larger scale. The rates of acidolysis were found to vary with different lipase sources. Generally both the T. Lanoginosa and Alcaligenes sp. lipases also produced the highest degree of acidolysis and % FFA, with oleic acid content up to about 60 %. Both lipase-catalysed mixtures cause the lift in slip melting point and solid fat content (SFC) at a higher temperature (above 25 °C) in all the two mixtures studied compared to the unreacted commercial olein. The second part of this study, was studied the factors affecting the transesterification of palm olein with methyl oleate. Both lipases were used in acidolysis as a model to study the effect of temperature, lipase loading, substrate concentration and reaction time. The optimum condition for transesterification was at 50 °C, 10% (w/w) lipase load, substrate concentration of 1:2 (POo:MO mole ratio) and 2 h incubation time for both lipases. Similarly, the transesterification process also increased the SMP of palm olein after 2 h reaction with T. Lanoginosa lipase registering increase of 1.3 °C compared to the initial unreacted mixture. The SMP and SFC results share the similar trend with acidolysis, while the oleic acid content generated from transesterification was about 54 %, slightly lower than acidolysis. Generally, the products obtained from interesterification contained higher oleic acid compared to that of starting POo (about 42-46%). Therefore, interesterification process without any further treatment, has improved the unsaturation of a palm oil product as well as monounsaturation content, which is comparable to olive oil.